Knowledge management in the Brazilian public service: A review under the methodological optics - Parreiras, Elaine Martins; Nascimento Silva, Patrícia (Advanced Notes in Information Science, 2024)
The field of knowledge management (KM) is situated within the broader domain of information science. It is concerned with the generation and dissemination of knowledge and its role in fostering innovation and competitiveness. In the context of public service, KM refers to the organization and processing of information with the aim of facilitating its sharing with the relevant teams, thereby enhancing institutional productivity and the efficiency of service delivery to citizens. The objective of this study was to conduct a brief bibliographical review of KM in the public sector within the context of information science, with a particular focus on the methodological instruments recently employed in Brazil. This was done with the aim of delineating the methodological approaches used in research on KM in the public sector. Accordingly, a bibliographic research was conducted in the Portal of Periodicals of the Coordination of Higher Education Personnel Training (CAPES) in August 2023, with a time frame encompassing the previous five years (2019–2023). The result was a mapping of 25 works, categorized according to the following methodologies: case/field study, documentary research and literature review, survey, bibliometric research, and use of models in the most diverse public institutions in Brazil. The value of this work lies in its ability to synthesize the diverse methodologies employed in the field of KM within the Brazilian public sector. It provides researchers with a comprehensive overview of the avenues they can pursue in their future studies. As future research endeavors, it is recommended that the investigation be continued, with a particular focus on the distinctive characteristics of the methodologies in question.